Methamphetamine-induced nitric oxide promotes vesicular transport in blood–brain barrier endothelial cells - Martins, Tânia (Pergamon Press, 2013)
Methamphetamine's (METH) neurotoxicity is thought to be in part due to its ability to induce blood–brain barrier (BBB) dysfunction. Here, we investigated the effect of METH on barrier properties of cultured rat primary brain microvascular endothelial cells (BMVECs). Transendothelial flux doubled in response to METH, irrespective of the size of tracer used. At the same time, transendothelial electrical resistance was unchanged as was the ultrastructural appearance of inter-endothelial junctions and the distribution of key junction proteins, suggesting that METH promoted vesicular but not junctional transport. Indeed, METH significantly increased uptake of horseradish peroxidase into vesicular structures. METH also enhanced transendothelial migration of lymphocytes indicating that the endothelial barrier against both molecules and cells was compromised. Barrier breakdown was only observed in response to METH at low micromolar concentrations, with enhanced vesicular uptake peaking at 1 μM METH. The BMVEC response to METH also involved rapid activation of endothelial nitric oxide synthase and its inhibition abrogated METH-induced permeability and lymphocyte migration, indicating that nitric oxide was a key mediator of BBB disruption in response to METH. This study underlines the key role of nitric oxide in BBB function and describes a novel mechanism of drug-induced fluid-phase transcytosis at the BBB.